Clinical Incidence of Diseases in Cattle and Goat at Different Area of Bera Upzilla in Pabna District of Bangladesh (Journal of Scientific Research, 2021)
Ruminant, especially cattle and goats constitute the major portion of the livestock which are usually suffered from a wide range of diseases. Hence, this study was designed to determine clinical cases of cattle and goat in relation to different parameter. A total of 106 sick ruminants (cattle = 56, goat = 50) in different area of Bera upzilla, Pabna were investigated during March to September, 2016. The parasitic infestation (32.1%) in cattle and viral diseases (36%) in goat were higher. In relation to sex, the disease frequencies were higher in female goat of 56.0% and reproductive diseases in female cattle of 66.7%. Among the clinical case, 70% was in black bangle goat. On the other side, the vaccination and grazing system had strong significant (p